PENGARUH KEADILAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJAPEGAWAI PADA PUSKESMAS MATANG SURI KABUPATEN SAMBAS - RAJIMIN B2042142013 (Universitas Tanjungpura, 2017)
Research conducted at the health center Suri Mature Sambas district pertaining about the influence of organizational justice on organizational citizenship behavior and performance. This relates to terselengaranya good health services also depends on the adequacy of health resources. With healthcare resources in accordance with established standards, the health service is expected to run well and in the end produce quality health services and satisfy all parties. This has an impact on improving the performance of employees working in the field of health care.The purpose of this study was to examine and analyze the influence of organizational justice on organizational citizenship behavior and performance of employees Mature Suri Sambas district health center. Forms of this research is to use Causal research. Collecting data using primary data in the form of questionnaires and interviews and secondary data sourced from the Office of the District Perindagkoptamben Mempawah. Sample using a sample census. The sample in this study is overall employee at the health center Matang Suri in Sambas district as many as 46 people.The results of this study showed that organizational justice a significant positive effect on organizational citizenship behavior of employees health center Matang Suri in Sambas district. Both organizational fairness significant positive effect on employee health center kenerja Mature Suri in Sambas district. The third organizational citizenship behavior significantly positive effect on employee health center kenerja Mature Suri in Sambas district. Keywords: Organizational Justice, Organizational Citizenship Behavior And Performance.